Self‐adaptive form generation method for reciprocal grid structures. (12th November 2018) - Su, Yan; Wu, Yue; Qiao, Gang; Shen, Shizhao
Abstract: Reciprocal grid structure is a structural system consisting of mutually supporting bars. Its geometry should satisfy not only the demands of architectural intents but also the requirements of the lapping relationship of the bars. Thus, form generation is the key problem in its design. Inspired by the physical building process of a reciprocal grid structure, self‐adaptive form generation method is proposed. In this method, an initial plane grid with the topology of required structural configuration is created first. Next, elements are iteratively lapped to realize a self‐adaptive generation of structural form. Two new parameters, bar lapping factor and rotation angle, are proposed to describe reciprocal grid structures quantitatively and make the form generation process easy. The efficiency and accuracy of the method are illustrated by comparisons with other form generation methods. Numerical examples demonstrate the applicability of the proposed method in the complex and realistic reciprocal grid structures.